An evaluation of gravity waves and gravity wave sources in the Southern Hemisphere in a 7 km global climate simulation. (23rd August 2017) - Holt, L. A.; Alexander, M. J.; Coy, L.; Liu, C.; Molod, A.; Putman, W.; Pawson, S.
Abstract : In this study, gravity waves (GWs) in the high‐resolution GEOS‐5 Nature Run are first evaluated with respect to satellite and other model results. Southern Hemisphere winter sources of non‐orographic GWs in the model are then investigated by linking measures of tropospheric non‐orographic gravity wave generation tied to precipitation and frontogenesis with absolute gravity wave momentum flux in the lower stratosphere. Finally, non‐orographic GW momentum flux is compared to orographic gravity wave momentum flux and compared to previous estimates. The results show that the global patterns in GW amplitude, horizontal wavelength, and propagation direction are realistic compared to observations. However, as in other global models, the amplitudes are weaker and horizontal wavelengths longer than observed. The global patterns in absolute GW momentum flux also agree well with previous model and observational estimates. The evaluation of model non‐orographic GW sources in the Southern Hemisphere winter shows that strong intermittent precipitation (greater than 10 mm h −1 ) is associated with GW momentum flux over the South Pacific, whereas frontogenesis and less intermittent, lower precipitation rates (less than 10 mm h −1 ) are associated with GW momentum flux near 60°S. In the model, orographic GWs contribute almost exclusively to a peak in zonal mean momentum flux between 70 and 75°S, while non‐orographic waves dominate at 60°S, and non‐orographic GWs contribute a third to a peak in zonal mean momentum flux between 25 and 30°S. Abstract : Small‐scale gravity waves like the ones shown here from the high‐resolution climate simulation used in this study are important drivers of circulation and transport in the middle atmosphere, and they are currently included in most climate models via parametrizations. However, parametrizations remain poorly constrained because the relative importance of different gravity wave sources is still not completely understood. This study utilizes a high‐resolution climate simulation which resolves much of the gravity wave spectrum to link gravity waves to their sources.